Effects of drought stress on early white pine blister rust development in limber pine - Bertram, Jonathan H., author; Stewart, Jane E., advisor; Scoettle, Anna W., advisor; Borlee, Brad, committee member; Ocheltree, Troy, committee member (Colorado State University. Libraries, 2022)
Climate change and forest pathogens are expected to interact as incidences of drought increase and affect the disease triangle between hosts, pathogens, and the environment. Trees will become physiologically affected by drought stress and primary pathogens such as fungal biotrophs will experience drought stress as mediated through the host. White pine blister rust, caused by the non-native pathogen Cronartium ribicola, is a devastating fungal pathogen, and little is known about how it will perform (measured by fungal growth or disease severity) within pine hosts experiencing unusual drought. This study aimed to address some of the unknown aspects of this interaction by performing a greenhouse drought × pathogen experiment with Pinus flexilis seedlings, measuring host physiology, quantifying specific aspects of pathogen performance, and looking for interactive effects. Watering treatments consisting of well-watered, mild chronic drought, or severe acute drought were applied to 432 seedlings; after 3 months, a subset of 198 seedlings were inoculated with C. ribicola basidiospores under ideal inoculation conditions, after which watering treatments continued for a further 9 months. Specific rust performance measurements included mycelial growth via relative rust DNA quantification and ratings of disease severity by watering treatment.
Keywords: drought; qPCR; pine physiology; blister rust